Recovery among People with Mental Illness (PMI) as Perceived by the Caregivers in Islamic Boarding School (IBS) in Indonesia - Sarjana, Widodo; Fitrikasari, Alifiati; Sari, Sri Padma (Department of Nursing, Faculty of Medicine, Diponegoro University, 2015)
Background: Mental hospitals as places to rehabilitation people with mental illness(PMI) in Indonesia are limited in numbers and do not meet with the number of PMI.The society may contribute in facilitating recovery and rehabilitation place for PMI including Islamic boarding school. Some Islamic boarding schools provide rehabilitation for PMI to help with recovery process. Recovery is an important aspect to assess the success of PMI rehabilitation. Nevertheless, there has been no study on Islamic boarding school’s caregivers’ perception on PMI recovery.Purpose: This study aims to explore recovery perception of caregivers treating PMI in Islamic boarding school and factors affecting recovery.Methods: Data are acquired from 19 caregivers from three Islamic boarding schools providing rehabilitation for PMI with Focus Group Discussion (FGD). The data analyzed using descriptive analysis.Result: Having a good communication is a recovery criterion that is mentioned themost by caregivers. There are three biggest factors affecting recovery based on the caregivers such as prayers or religion followed by social support from family and environment and also doing activities.Conclusion: The results may depict the PMI recovery so that the health care providers can provide interventions that can support the recovery process in PMI.